الحرب ا الأمريكية علي العراق وموقف العالم الأسلامي منها - Abedi Ahmed Mukhtar (Universiti Sains Islam Malaysia, 2024)
Thesis (M.A) - Faculty of Leadership and Management, Universiti Sains Islam Malaysia, 2014.